Analysis of Determinants of Students' Physical Conditions in Urban and Rural Environments - Raehan Fathur Farhanu; Hijrah Maulidiah Afifah (Universitas Negeri Semarang, 2026)
This study aims to analyze the determinants of students' physical condition in urban and rural environments in Semarang. The study used a quantitative, correlational method. The study sample consisted of 67 students, consisting of 33 rural students and 34 urban students, selected using a purposive sampling technique. Data collection was carried out using the Neighborhood Environment Walkability Scale-Youth (NEWS-Y) questionnaire, anthropometric measurements, and the Nusantara Student Fitness Test (TKPN), which includes V Sit Reach, Sit Up, Squat Thrust, and PACER. Data analysis used descriptive statistics, normality and linearity tests, and Pearson Product-Moment correlation tests with SPSS version 26. The results showed that most students in both schools were in the category of sufficient physical fitness. Urban students had higher average TKPN scores than rural students across all test components. The results of the correlation test showed that the relationship between environmental determinants and students' physical condition was 0.110 in rural areas (p=0.541) and 0.080 in urban areas (p=0.654). These results indicate that the relationship between environmental determinants and students' physical condition is very low and insignificant. This study indicates that students' physical condition is influenced by various factors such as daily physical activity, nutritional status, modern lifestyle, and active lifestyle habits.